Nephroprotective effect of hygrophila spinosa and mangifera indica in albino rats - Bibu John Kariyil (Department of Pharmacology and Toxicology, College of Veterinary and Animal Sciences, 2007)
The present study was undertaken to assess the nephroprotective effect of whole plant of Hygrophila spinosa and stem bark of Mangifera indica against gentamicin-induced nephrotoxicity in albino rats. The experiment was conducted for a period of 30 days. The animals were divided into ten groups comprising eight each. Group I served as healthy control which received vehicle alone. Groups II, III, IV, V, VI, VII, VIII, IX and X received gentamicin sulphate at a dose rate of 80 mg/kg i.p. for eight days. Group II was retained as such without any treatment till the completion of the experiment. Group III and Group IV received ethanolic extracts of Hygrophila spinosa at a dose rate of 50 mg/kg p.o. and 250 mg/kg p.o. respectively whereas Group V and Group VI received aqueous extracts of Hygrophila spinosa at a dose rate of 50 mg/kg p.o. and 250 mg/kg p.o. respectively. Group VII and Group VIII received ethanolic extracts of Mangifera indica at a dose rate of 100 mg/kg p.o. and 500 mg/kg p.o. respectively while Group IX and Group X received aqueous extracts of Mangifera indica at a dose rate of 100 mg/kg p.o. and 500 mg/kg p.o. respectively. The blood samples were collected on 0th, 9th, 15th and 30th day and serum was used for the estimation of creatinine, urea, albumin, total protein, sodium, potassium and calcium. On 30th day, all the animals were sacrificed and kidney was used for the estimation of superoxide dismutase, lipid peroxidation, catalase and reduced glutathione. Histopathological studies were also conducted to assess the nephroprotective action of these plant extracts. Administration of the herbal extracts at various dose levels brought about a significant reduction in lipid peroxidation and an increase in the activities of superoxide dismutase, catalase and reduced glutathione, which suggest its efficacy in scavenging free radical-induced renal damage. Treatment with ethanolic extract of Hygrophila spinosa at the dose rate of 250 mg/kg was found to be the most effective treatment in scavenging the free radical-induced gentamicin nephrotoxicity. Treatment with the plant extracts showed a decreased creatinine level following gentamicin administration. The serum urea levels were significantly reduced in all the treatment groups. The significant reduction in serum urea levels was predominant in ethanolic extract of Hygrophila spinosa at the dose rate of 250 mg/kg and aqueous extracts of Mangifera indica. The most significant reduction in serum creatinine and serum urea levels was shown by ethanolic extract of Hygrophila spinosa at the dose rate of 250 mg/kg. Serum levels of albumin, total protein, sodium, potassium and calcium were within the normal range throughout the experiment. The results were substantiated by histopathological studies, which confirmed that treatment with ethanolic and aqueous extracts of Hygrophila spinosa and Mangifera indica inhibited gentamicin-induced proximal tubular necrosis. Ethanolic extract of Hygrophila spinosa at the dose rate of 250 mg/kg was found to be most effective in favouring nephroprotection. Phytochemical analysis of plant extracts revealed the presence of steroids, phenolic compounds, tannins, flavonoids, glycosides, diterpenes and saponins. The findings of the present study validate the nephroprotective effect of Hygrophila spinosa and Mangifera indica for the management of renal disorders.